ANALISIS KOMPARATIF PENDAPATAN USAHATANI PADI SAWAH TADAH HUJAN ANGGOTA DAN NON ANGGOTA KELOMPOK TANI DI DESA HARAPAN MULIA KECAMATAN SUKADANAKABUPATEN KAYONG UTARA - Saupi, Muhammad; Yusra, Abudl Hamid A.; Hidayat, Rakhmad (Jurnal Sains Mahasiswa Pertanian, 2019)
This research was motivated by good prospect of rice commodity to increase income of farmer at Harapan Mulia village. The purpose of the research is to find out income level difference between rain containing rice field farmer that is member of farmer group and the rain containing rice field farmer that is not member of farmer group at Harapan Mulia village. Populations of the research are rain containing rice field farmer that is member and outsider of farmer group at Harapan Mulia village, with respondent 36 people of farmer group and 20 people that is not farmer group member. Analysis used is comparative independent sample t test. The result shows no significant difference of income between rain containing rice field farmer that are member of farmer group and outsider of farmer group at Harapan Mulia villageKeyword : farmer work income, rice, comparative